Induction motor drive based on modular-multilevel converter with ripple-power decoupling channels - Enaam Abdul-Khaliq Ali; Turki Kahawish Hassan (Institute of Advanced Engineering and Science, 2022)
A driving system for a three-phase variable-speed induction machine-based modular multilevel converter (MMC) with magnetic channels operating at high frequencies -connecting adjacent-arm submodules is displayed in this paper. The primary disadvantage of using MMC in variable-speed motors is a high voltage ripple generated by submodule capacitors at low speeds with constant torque. This study utilises the DHB modules as energy channels, exchanging between the SM capacitors to correct the power imbalance. The ripple power of adjacent-arm SMs may be entirely decoupled, outcomes a virtually fluctuation-set free SM capacitor voltage design. Thus, the typical MMC issue of significant ripple voltage between SM capacitors has been wholly addressed regardless of operating frequency. The design and analysis of Field Oriented Control (FOC) of induction motors is based on an algorithm that ensures the motor's efficiency across a broad speed range. In this paper, we achieved a tiny ripple in the capacitive voltage for some frequencies (50Hz, 25Hz, 10Hz, 5Hz) by (±0.25%) compared with the previous papers that achieved a reduction in ripple within (±5%), and also this system was compared with the traditional system method operating principle was presented analytically and verified using Matlab Simulink.